Risk Factors and Practices for the Development of Open Source Software From Developers’ Perspective - Shehzad Haider (17541825) (2023)
Open source software (OSS) has achieved popularity, however there are various software product quality problems, security issues and certain challenges confronting the OSS growth that need to be identified and addressed. The main focus of this research is to identify the risk factors associated with open-source software and the practices for those risks which will help software development companies and individuals to mitigate the risks. A systematic literature review (SLR) is employed for the identification of potential risk factors in OSS whereas questionnaire survey is used to validate the findings of the SLR from the relevant expert community. In the second round another SLR is carried out to identify the practices for softening the effect of risk-factors in OSS development. A total of 14 risk factors from the developers’ perspective are identified via SLR in OSS. Amid the risk factors identified bugs, insufficient product documentation, and lack of communication and coordination among developers are considered the most important Further, we performed a secondary SLR to identify the practices for mitigating the effects of the risk factors in OSS. Therefore, a total of 31 practices for mitigating and addressing the risk factors in OSS were identified. In this work, we identified 14 risk factors and 31 practices for mitigating the critical risk factors, through SLR for adapting OSS development from developers’ perspectives. We argue that focusing on the identified risk factors would minimize the risks associated with OSS. We also recommend that OSS developers should diligently consider all the risk factors that have been identified in the study for increased software productivity and distribution of reliable and robust source code. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3267048